Encouraging Learning Autonomy through Differentiated Instruction in Writing Activities - Hernina Dewi Lestari; Adi Adi; Yahmun Yahmun (UIBU, 2024)
This classroom action research seeks to demonstrate how differentiated instruction might promote students' learning autonomy in a writing class setting. This study included 50 English department students from a private institution in Malang. According to the findings of the preliminary study, students were unmotivated to participate in writing activities because they thought they were boring and uninteresting. They were detected paying little attention to the assigned writing assignments and, as a result, demonstrating poor writing performance. To promote student learning autonomy, the researchers implemented with differentiated instructions in several writing exercises. Using two cycles of classroom action research, the researchers seek to solve the instructional challenge using potential learning strategies. After adopting differentiated instruction, the researchers assessed the students' writing scores and compared them to success criteria. The first cycle resulted in 70% of students meeting the success criterion since they were still unfamiliar with the differentiated instructions. In the second round, the pupils successfully met 85% of the criteria. The findings showed that creating differentiated instructions provided pupils with a favorable challenge. It was evident from the behavioral changes of pupils who exhibited greater enthusiasm for following the directions. Furthermore, the students demonstrated the established learning autonomy, which resulted in improved writing performance. These research findings add to the enrichment of the educational component, since future teachers or researchers may focus on a more comprehensive covering of this teaching technique.